Differential equations, dynamical systems, and linear algebra: By Morris W. Hirsch and Stephen Smale - Hirsch, Morris; Smale, Stephen (Academic Press, 1974)
This book is about dynamical aspects of ordinary differential equations and the relations between dynamical systems and certain fields outside pure mathematics. A prominent role is played by the structure theory of linear operators on finite-dimensional vector spaces the authors have included a self-contained treatment of that subject.